A systematic review of proaporphine alkaloids and a pharmacological update - Christian Bailly (Phytomedicine Plus)
Background: Proaporphine alkaloids are present in many plant families. They are often considered as metabolic precursors to aporphines. They generally contain a cyclohexadienone system and can rearrange to aporphines on treatment with acid. Typical proaporphines include the alkaloids pronuciferine, stepharine, crotsparine, glaziovine and many analogues with different substitution patterns. The proaporphine glaziovine has been used in human as a tranquilizer to treat anxiety and depression but otherwise proaporphines have received little attention as medicinal products. Proaporphines have been neglected compared to aporphines. Purpose: The present review provides a survey of a hundred of proaporphine alkaloids isolated from plants, divided into three groups: conventional proaporphines (including mecambrine, roemeronine and orientalinone among others), homoproaporphines with a tetracyclic or pentacyclic core (such as kreysiginone and robustamine), and various proaporphine hybrid molecules (roemeridine, magnostepharine and diverse analogues). Results: The structural diversity of proaporphines is presented. The properties of prototypic proaporphine alkaloids are discussed, and their mechanisms of action are underlined. The case of atypical but promising proaporphine dimers, such as distepharinamide targeting tumor infiltrating T regulatory cells, is also addressed. Conclusion: The analysis offers a survey of the proaporphine landscape with the goal to highlight the molecular diversity in the family and to encourage further researches into their mechanism of action and medicinal properties.